Work-related risk factors for asthenopia among employees: a 2024 study - Pratami, Tiara putri; Linda, Ony; Muzakir, Hariz (Jurnal Cakrawala Promkes, 2025)
Asthenopia, or eye strain, is a common occupational health issue that can negatively impact employee productivity. This study aimed to analyze occupational factors associated with asthenopia among office-based employees in 2024. A cross-sectional analytical design was employed, involving 61 respondents. Data were collected using a structured questionnaire to assess variables such as age, sex, years of employment, eye rest habits, and duration of computer or laptop use. The distance between the eyes and the computer/laptop was measured with a measuring tape, and lighting intensity at workstations was assessed using a luxmeter. Statistical analysis was conducted using the chi-squared test and Fisher’s exact test. The results showed that 70.5% of respondents experienced asthenopia. Significant associations were found between asthenopia and age (p = 0.011), eye rest (p = 0.007), duration of computer/laptop use (p = 0.018), screen distance (p = 0.031), and lighting intensity (p = 0.006). No significant association was found between asthenopia and sex or years of employment. Based on these findings, routine eye examinations and the implementation of eye rest techniques are recommended, particularly for employees over the age of 40. Employers are also encouraged to implement promotive measures, including the provision of visual aids, ergonomic workstations, standing desk options, and improved lighting using LED daylight lamps.